Tuned in: the importance of peer feedback with foster youth creating media. Issue 5 (2nd September 2020) - Friesem, Yonty; Greene, Kelsey
ABSTRACT: This longitudinal qualitative research explores the benefits and challenges of using positive peer feedback with a group of foster adolescents during a summer academy at a Northeastern university. In addition, the authors, who taught the class for four years between 2012–2015 reflect on their experience using the structured feedback as a tool in their digital and media literacy class. The paper describes how the instructors addressed challenges revolving around students' social, emotional, and cognitive needs through the incorporation of peer feedback. Based on positive behavior support and peer mentoring, the authors used a structured peer feedback as part of their digital and media literacy pedagogy. The findings show that students' use of peer feedback with different media platforms helped increase the students' engagement, develop collaboration skills and for some enhance their critical thinking. As we move to use more and more digital tools, this method of positive peer feedback can help educators to grow their students' social, emotional, and cognitive skills.